A study of the competitiveness of the Spanish construction industry. (15th November 2004) - Parreno Fernandez, Jose; Ordonez de Pablos, Patricia
This study has a two-fold objective. First, it sets out to describe the present situation of the Spanish construction industry and its importance for the competitiveness of the national economy. It then goes on to consider the issue of forecasting for this strategically important sector, by considering three time series – total amount of tendering, the consumption of cement and the total number of homes built – and then forecasting by applying the Box-Jenkins methodology. The comparison of ex-post forecasts with the real data for the three variables, provides a way to evaluate the goodness of the models selected for forecasting.